The puppet theater of Tía Norica of Cádiz as cultural heritage: a material and immaterial tradition. (Móin-Móin Magazine - Studies in the Art of Puppetry, 2023)
The Tía Norica puppet theater in Cádiz (Spain) has been part of the city's cultural heritage for two centuries. This theater is characterized by its particular repertoire and by the technique of its shows (marionettes, rod and string puppets), heirs of the real machine. Various companies have maintained this tradition over time, sometimes simultaneously, generating a material heritage that today is partially preserved in the Museum of Cádiz. It also continues to be a living heritage, since a company has existed since 1984 that, with copies of the Museum's puppets, has continued to represent the traditional repertoire to this day. The conservation of this patrimony, tangible and intangible, must be a cultural priority in an increasingly globalized and uniform society.
Keywords: marionettes; tangible patrimony; intangible patrimony